A descriptive study defining perceptions of selected Filipino respondents on the concepts of a motel in the Philippines - De Guzman, Frances K.
ABSTRACT Motels may have different connotations based on where they are and how they are introduced in the market. This study sought to determine how selected Filipino respondents perceive the primary functions of a motel in the Philippines and clarify whether the respondents' perceptions on the concept on motels in the Philippines are aligned with the traditional function of a lodging facility.